Perbandingan Efektivitas dan Keamanan Obat Flutikason dan Amoksisilin dalam Mengatasi Sinusitis Akut pada Anak-Anak: Sebuah Tinjauan Sistematik Mini - Munir Alinu Mulki; Eriyanti Astika; Sulistiawati Sulistiawati; Aldila Divana Sarie; Anisa Aula Rahma; Fikri Aldebaran Misbah Azizi; Karlina Dwi Samratul Jannah (Journal of Pharmaceutical and Sciences, 2023)
Acute sinusitis (AS) can be defined as inflammation of the nose due to infection of the preanal sinus. Sinusitis is a common condition that occurs in children. Children experience an average of 6-8 colds per year with 0.5-5% developing acute sinusitis infection. Nasal corticosteroid drugs that are often used for sinusitis therapy are fluticasone. Not only that, antibiotic class drugs can also be used for the treatment of acute sinusitis, one of which is amoxicillin. The purpose of making this systematic review is to determine the effectiveness and combination of fluticasone and amoxicillin drugs in dealing with acute sinusitis treatment problems. The literature search was conducted electronically at PUBMED and was in accordance with the protocol made by PRISMA in conducting this systematic review. The literature search was conducted electronically for articles published in the last 10 years (from January 2013 to May 2023) and specific keywords 1. "acute sinusitis", OR 2. "fluticasone", OR 3. "amoxicillin", AND 4. "children" were used in the search. Inclusion criteria included experimental study design (randomized controlled trial). Articles were excluded according to case-control, cohort or qualitative study types. The data to be retrieved were the study population, type of intervention performed, study design, control variables, as well as the conclusions of the study. The article found 22 journals in the search strategy. In the end, there were 3 journals that met the eligibility criteria and were included in this systematic review. The three studies explained that the combination of fluticasone and amoxicillin had a more effective effect than monotherapy.